The scaffold protein p140Cap limits ERBB2-mediated breast cancer progression interfering with Rac GTPase-controlled circuitries - Silvia Grasso (Nature Portfolio, 2017)
p140Cap adaptor proteins interfere with adhesion and growth factor-dependent signalling in cancer cells but the mechanisms are unclear. Here the authors show that p140Cap interferes with ERBB2-dependent activation of Rac GTPase-controlled circuitries reducing metastasis and cancer progression.